Zooplankton Fluctuations in the Surface Waters of the Estuary of a Large Subtropical Urban River - Lee, Pei-Wen; Hsiao, Shih-Hui; Chou, Chi; Tseng, Li-Chun; Hwang, Jiang-Shiou (Frontiers in Ecology and Evolution, 2021)
The Danshuei River has the third largest catchment area and third-longest in Taiwan. It flows through the capital, Taipei, and more than 6 million people live within its catchment area. Its estuary is characterized by a highly variable chemical and physical environment that is affected by the interaction of inland freshwater runoff with wastewater, and towards the coast is also influenced by the China Coastal Current and the Kuroshio Current. By collecting zooplankton bimonthly in 2014 from the surface layer (0–2 m depth) at five sites in the estuary, we were able to demonstrate that the composition of the zooplankton, and particularly its copepod fraction, varied significantly among sampling stations and months, thereby revealing seasonal succession. Fourteen higher taxa or other categories of zooplankter were identified, with the following being most common taxa: Decapoda, Copepoda (including Calanoida, Cyclopoida, and Harpacticoida), and “other larvae”. The Copepoda comprised 44 taxa (including 8 only identified to genus) belonging to 3 orders, 17 families, and 29 genera, the 5 most abundant of which were Bestiolina n. sp. (undescribed), Corycaeus spp., Parvocalanus crassirostris, Acartia sp., and Paracalanus parvus. The highest and lowest copepod abundances were recorded in July (2557.88 inds. m-3) and January (1.3 inds. m-3), respectively. Observed changes in abundance of many kinds of copepod appeared to be significantly related to changes in physico-chemical parameters (e.g., salinity, temperature, pH, and dissolved oxygen concentration). Cluster analysis confirmed the existence of distinct copepod communities, each characterized by a preference for a different set of environmental conditions. Our comprehensive literature review of the copepod biodiversity of Taiwan’s major rivers for comparison with similar data compiled for other estuaries in the world, the first time such a review has been compiled, shows that 32 copepod taxa have been recorded from the brackish and freshwater parts of the Danshuei River. They represent 58.2% of the total number of brackish- and freshwater copepod species in Taiwan, and 5 of them have so far only been recorded in the Danshuei River: the calanoids Acartiella sinensis and Pseudodiaptomus forbesi, the cyclopoids Oithona fragilis and Oithona simplex, and the harpacticoid Tachidius discipes.